Sleep apnoea syndrome: states of sleep and autonomic dysfunction. - Gulleminault, C (1977)
Eleven patients with upper airway apnoea during sleep (one with SHY-Drager syndrome) were monitored polygraphically for wakefulness, sleep, and cardiovascular variables. Systemic hypertension and most of the severe arrhythmias recorded during sleep were secondary to repetitive obstructive apnonea and were mediated through the autonomic nervous system. Sleep related elevations of pulmonary arterial pressure were not influenced by atropine or impaired autonomic functions. Upper airway sleep apnoea is sleep related; the type of sleep (REM or NREM) is critical in the appearance of abnormalities. The distinction between two patient subgroups (total sleep dependent and NREM sleep dependent) has haemodynamic, and possibly long-term, implications. Sleep apnoea syndrome should be looked for in pateints with the Shy-Drager syndrome.